Genetic diversity in Nigeria taro [Colocasia esculenta (L.) Schott] germplasm - Oladimeji, J.J. (2025)
Taro is a resilient, underexploited tropical corm-producing crop that plays a vital role in the nutritional and economic livelihoods of many households in Nigeria. However, its production and productivity are constrained by the incidence of diseases, low-input farming practices and inadequate genetic improvement efforts. To improve the yield and quality of taro in Nigeria, adequate information is needed on the presence of heritable genetic variation among available collections. However, limited information is available on the level of variability among cultivated taro in Nigeria. This study was carried out to assess the extent of phenotypic and molecular diversity among some taro accessions collected from major taro-growing agroecologies in Nigeria. Four hundred and ninety taro landraces comprising 215 Dasheen and 275 Eddoe gene pools were assembled from farms and markets across seven States (Oyo, Kwara, Ekiti, Ondo, Akwa Ibom, Ebonyi and Anambra) in humid forest and derived savanna agroecologies in Nigeria. The 490 landraces were genotyped using 4,748 Diversity Array Technology sequence-based Single Nucleotide Polymorphism (DArTseq-SNP) markers, 3,047 of which were retained after quality filtering. A subset (114) comprising 65 landraces from the first collection and 49 landraces from the second collection were planted in September 2021 and March 2022 respectively, following their collection times using 27 agromorphological descriptors. Phenotypic data were subjected to descriptive statistics, cluster analysis and analysis of variance, while hierarchical clustering, population structure and analysis of molecular variance were carried out on the molecular data. The phenotypic and molecular characterization of the taro landraces revealed higher genetic diversity among the Eddoes than among the Dasheens. For all the quantitative traits, the estimates of genetic variance were higher than those of environmental variance. The total yield (TY) of the landraces ranged from 100 to 32,200 kg/ha (mean = 10,600kg/ha) for the phenotyped September 2021 set while the range was from 100 to 23,300kg/ha (mean = 6,800 kg/ha) for the March 2022 set. The taro landraces in both planting clustered into four groups based on 10 phenotypic traits at a threshold of 1.5. Highest yield was recorded in K-I-O1-S1 and A-I-IE Cormel 1 (32,200 kg/ha) from the September 2021 planting and AKN 1-P5 (23,300 kg/ha) from the March 2022 planting. Estimates of gene flow (Nm = 0.353) revealed intermixing of landraces among the States of collection. Gene flow was highest (1458.98) between landraces from Anambra and Ondo States and lowest (0.06) between Anambra and Kwara States. The population structure and hierarchical clustering based on the DArTseq-SNP markers delineated four clusters, one which comprised Dasheens, while three comprised Eddoes. The variation between gene pools (49%) was higher than within gene pools (32%). The variation among the States of collection was high (41%), while the variation among individuals within the gene pools (18%) and States of collection (19%) were relatively low. A wide level of genetic diversity was found between the taro gene pools and among the taro landraces from Nigeria. The findings constitute a valuable resource for the genetic improvement of taro in Nigeria.